Rehabilitation of underutilized sandy soils by agroforestry and organic amendments - Abu Bakar, Rosenani; Hashim, Azizah; Nik Ab. Majid, Nik Muhamad; Ab Shukor, Nor Aini; Ibrahim, Faridah Hanum (1993)
A collaborated and integrated project was started in 1992 to investigate the feasibility of rehabilitating the tin tailings and BRIS soils of Malaysian through agroforestry and organic amendments. Three studies were proposed on the tin-tailing soil,mainly to test timber species suitability,performance of tree crops in association with agricultural crops and pasture,and growth response of the timber species to mycorrhizal inoculation. Two of the studies had already started in 1992 and 1993. Only one study was proposed for BRIS soil and the field experiment was set up in early 1992. All the studies are currently being monitored and some data have already been obtained.